2019
DOI: 10.4093/dmj.2018.0134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sodium-Glucose Cotransporter-2 Inhibitors in Korean Patients with Type 2 Diabetes Mellitus in Real-World Clinical Practice

Abstract: BackgroundThis study aimed to evaluate the efficacy and safety of sodium-glucose cotransporter-2 (SGLT2) inhibitors in Korean patients who had inadequately controlled type 2 diabetes mellitus (T2DM) in real-world clinical practice.MethodsWe included 410 patients who started SGLT2 inhibitors (empagliflozin or dapagliflozin) as add-on therapy or switch therapy between February 2015 and June 2017. The primary efficacy endpoint was a change in glycosylated hemoglobin (HbA1c) from baseline to week 12. The secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 46 publications
3
24
2
Order By: Relevance
“…inhibitors presented with relatively higher HOMA than the group responding poorly to SGLT2 inhibitors. Nevertheless, the HOMA-β level was not associated with SGLT2 inhibitor responsiveness [28]. The results of this study suggested that SGLT2 inhibitors improved insulin resistance but not insulin secretion in the pancreatic β-cells of T2DM patients.…”
Section: Discussionmentioning
confidence: 52%
“…inhibitors presented with relatively higher HOMA than the group responding poorly to SGLT2 inhibitors. Nevertheless, the HOMA-β level was not associated with SGLT2 inhibitor responsiveness [28]. The results of this study suggested that SGLT2 inhibitors improved insulin resistance but not insulin secretion in the pancreatic β-cells of T2DM patients.…”
Section: Discussionmentioning
confidence: 52%
“…Regarding the effects of dapagliflozin by manners of initiation, we found patients who initiated dapagliflozin as add-on therapy had a significantly greater reduction in HbA1c (−0.82%) than those who were switched (−0.66%) from other OADs. Two recent studies also showed treatment with SGLT2 inhibitors (i.e., dapagliflozin or empagliflozin) as add-on therapy had a greater glucose-lowering effect than as switch therapy (Han et al, 2018;Hong et al, 2019). Notably, we found DPP4 inhibitors accounted for the majority (69.5%) of the switched agents (data not shown), a finding which is likely due to the fact that Taiwan's NHI only covers either a DPP4 inhibitor or an SGLT2 inhibitor.…”
Section: Notesmentioning
confidence: 47%
“…In general, studies suggest that patients with higher baseline HbA1c experienced a greater reduction in HbA1c with dapagliflozin treatment (Brown, Gupta & Aronson, 2017;Han et al, 2018;Hong et al, 2019;Scheerer et al, 2016), and one study indicates that a lower baseline HbA1c was associated with the achievement of HbA1c goal (<7%) (Wilding et al, 2017). Other patient characteristics that may be associated with better dapagliflozin response were male (Brown, Gupta & Aronson, 2017), younger age (<45 years old) (Wilding et al, 2017), shorter disease duration (<2-4 years), (Brown, Gupta & Aronson, 2017;Wilding et al, 2017) and non-insulin use (Brown, Gupta & Aronson, 2017;Hong et al, 2019); however, some of these associations were not identified and other data were not available in the current study. On the other hand, baseline body weight or BMI did not influence the magnitude of reduction in HbA1c, which is similar to previous studies (Han et al, 2018;Scheerer et al, 2016;Wilding et al, 2017).…”
Section: Notesmentioning
confidence: 99%
“…In the present study, the addition of empagliflozin to metformin and sulfonylurea therapy for 12 weeks provided 0.87% reduction in HbA1c. 23 An investigation on effectiveness of SGLT2 inhibitors have shown a significant reduction in mean weight and HbA1c reduction 3.2 kg and 1.26%, respectively. 24 Based on four months follow-up, a study reported 0.7 % HbA1c reduction, weight dropped for an average −2.0 kg, SBP dropped significantly, but no change in DBP were observed.…”
Section: Discussionmentioning
confidence: 99%